Eco-mechanical performance of binary and ternary cement blends containing fly ash and slag. Issue 1 (21st August 2020) - Radwan, Mohammed K H; Onn, Chiu Chuen; Mo, Kim Hung; Yap, Soon Poh; Ng, Chee Guan; Yusoff, Sumiani
Abstract : It is becoming more common to replace cement partially with supplementary cementitious materials, which in turn influence the mechanical performance and environment impact of the resulting mortar or concrete. A study was undertaken to evaluate the eco-mechanical performance of both binary and ternary blended cement mortars. For this purpose, fly ash and ground granulated blast-furnace slag were used at various cement replacement levels. Ternary blended cements with up to 40% cement replacement exhibited both good flow and compressive strength performances compared with binary blended cements. From an environmental perspective, life-cycle assessment revealed that the major impacts of global-warming potential and fine-particulate-matter formation were mostly influenced by total cement replacement rather than by the type or replacement or blending combination. Similar observations were made for the eco-mechanical performance based on calculated warming-potential-to-strength and particulate-matter-to-strength ratios. Mortars containing 20 and 40% cement replacements demonstrated improvement in these aspects on average by about 20 and 40%, respectively. Overall, the study indicated that a 40% replacement level in a ternary blended cement is a viable eco-friendly solution for the cement industry.